Human mucosal‐associated invariant T (MAIT) cells possess capacity for B cell help. Issue 5 (1st November 2017) - Bennett, Michael S.; Trivedi, Shubhanshi; Iyer, Anita S.; Hale, J. Scott; Leung, Daniel T.
Abstract : Human MAIT cells have the capacity to provide help to B cells through induction of plasmablast differentiation and antibody production. Abstract : Mucosal‐associated invariant T (MAIT) cells are an innate‐like T cell subset, restricted by the nonclassic MHC class I‐related protein MR1 and enriched at mucosal sites. Human studies have shown an association between MAIT cells and pathogen‐specific antibody responses. In this study, we investigate the effect of human MAIT cells on B cells ex vivo. We found that supernatants from microbe‐ or cytokine‐stimulated MAIT cells, when added to purified autologous B cells, increase frequencies of plasmablasts and promote IgA, IgG, and IgM production. We found effects to be mostly MR1‐dependent and that the increases in plasmablasts are likely a result of increased differentiation from memory B cells. Furthermore, microbe‐activated MAIT cell supernatant contains multiple cytokines known to stimulate B cells, including IL‐6, ‐10, and ‐21. This study thus provides the first direct evidence of a newly identified role of MAIT cells in providing help to B cells.